Nephrology Referral in Diabetes Practice - Kalra, Sanjay; Sahay, Manisha; Sahay, Rakesh (Journal of Social Health and Diabetes, 2018)
Diabetic nephropathy, including diabetic kidney disease (DKD), is a major complication of diabetes. Appropriate management of DKD requires multispecialty intervention under the guidance of endocrinology and nephrology. However, delayed referral to specialized nephrology services usually occurs, and this leads to suboptimal outcomes. This multispecialty consensus suggests simple clinical and biochemical parameters that should prompt referral of DKD patients to nephrology. A checklist for physicians who manage DKD is also provided.
Keywords: chronic kidney disease; diabetic kidney disease; diabetic nephropathy; end-stage renal disease; type 1 diabetes; type 2 diabetes